Towards a new model for information warfare / Abdulrahman R. Alazmi - R. Alazmi, Abdulrahman (CMIWS and UiTM Press, 2014)
In the current information-rich environment, it has become routine to broadcast and receive information via the media and most importantly the Internet. And with such flexibility in the distribution of information and its channels comes the huge risk of the information being compromised, tampered with, or corrupted. Such intentional acts of compromising and corrupting information for a certain goal constitute what is known as Information Warfare. Because Information Warfare can be carried out on different forms of communication and channels in information flows, devising a model to simulate the attacks is vital to analyse and prevent information tampering. Many models have been proposed that use an array of underlying theories that range from schematic modelling, to information science and cognitive studies.